Magnetoplumbite type oxide as well as preparation method and application thereof
The sol-gel and molten salt method for preparing magnetoplumbite-type oxide addresses the electrocatalytic limitations of sulfur-based batteries, enhancing their performance through improved catalytic activity and stability.
Patent Information
- Application Number
- CN202411350681.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The industrialization of sulfur-based energy storage batteries is hindered by poor intrinsic conductivity and low utilization rate of sulfur, necessitating the development of advanced sulfur carriers to improve battery performance, particularly in terms of electrocatalytic activity and stability.
A magnetoplumbite-type oxide is prepared via a sol-gel method combined with a molten salt process, resulting in a powder with finer particles and uniform size distribution, enhancing electrocatalytic performance in sulfur reduction.
The prepared magnetoplumbite-type oxide exhibits strong catalytic activity, improving reaction kinetics and stable cycle performance of sulfur-based batteries, with a low-cost and wide application range.
Smart Images

Figure CN119160952A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic materials, and specifically relates to a magnetoplumbite-type oxide and a preparation method and application thereof. Background Art
[0002] Suffering from the problems of poor intrinsic conductivity and low utilization rate of sulfur, the industrialization prospects of sulfur-based energy storage batteries have been greatly weakened. In order to overcome these challenges, the development of advanced sulfur carriers is the key to improving battery performance (Nat. Nanotechnol. 2020, 15, 231).
[0003] Metal oxides with metal and oxygen vacancies have rich electronic structures, excellent mechanical properties, and strong coupling with sulfur. They can serve as solid sulfur sites to improve the stability of the battery and show excellent potential. However, liquid phase polysulfides have high affinity, which is not conducive to subsequent electrocatalytic conversion, so it is crucial to improve the intrinsic electrocatalytic activity of oxides (Energy Storage Mater. 2024, 67, 103315). Based on this, phase engineering is an effective strategy to improve the intrinsic electrocatalytic activity of materials. On the one hand, enriched heterogeneous phases and interfaces can serve as potential catalytic active sites to regulate the adsorption / desorption energy of intermediates (Chemical Reviews, 2024, 124, 1247). On the other hand, the control of vacancies and the implementation of topological ion exchange (TIE) can exhibit significant multiphase interactions and interfacial effects, further improving the catalytic activity of materials (Nat. Commun. 2023, 14, 5389).
[0004] In view of the above problems existing in the multi-phase / multi-state / multi-electron reaction of sulfur-based electrodes, how to improve the comprehensive performance of oxide sulfur storage batteries through phase engineering is still a difficult point. In order to solve the above problems, the present invention is thus developed. Summary of the invention
[0005] In response to at least one of the above-mentioned technical problems, the present invention provides a magnetoplumbite-type oxide and a preparation method and application thereof. The present invention first prepares a precursor by a sol-gel method, and then combines it with a molten salt method for high-temperature treatment to obtain a powder with finer particles and uniform particle size distribution; the magnetoplumbite-type oxide prepared by the present invention exhibits excellent electrocatalytic performance in the reduction process of sulfur, thereby obtaining theoretical support and technical breakthroughs for the practical application of magnetoplumbite-type oxide in sulfur reduction, thereby accelerating the practical application process of sulfur-based batteries.
[0006] The technical solution of the present invention is:
[0007] The present invention provides a method for preparing a magnetoplumbite-type oxide, comprising the following steps:
[0008] S1, dissolving rare earth nitrate Ln(NO3)3·6H2O, transition metal nitrates Me(NO3)2 and Al(NO3)3 in deionized water to obtain a mixed nitrate solution;
[0009] S2, adding citric acid monohydrate to the mixed nitrate solution obtained in step S1, heating and stirring, and evaporating to obtain a transparent gel;
[0010] S3, drying the gel obtained in step S2 to obtain a loose and porous dry gel;
[0011] The dry gel obtained in steps S4 and S3 is subjected to a first high temperature treatment at 650 to 950° C. in an air atmosphere to obtain a precursor;
[0012] S5. Grind and crush the precursor obtained in step S4, grind and mix it evenly with molten salt, and then perform a second high-temperature treatment at 1500-2000° C. in an air atmosphere to obtain a magnetoplumbite-type oxide.
[0013] Preferably, in step S1, the molar ratio of rare earth nitrate Ln(NO3)3·6H2O, transition metal nitrate Me(NO3)2 and Al(NO3)3 is 1:1:11; the total concentration of the prepared mixed nitrate solution is 0.01-1 g / L, that is, the total concentration of the three nitrates.
[0014] Preferably, in step S1, the rare earth nitrate Ln(NO3)3·6H2O is any one of Y(NO3)3·6H2O, La(NO3)3·6H2O, Pr(NO3)3·6H2O, Nd(NO3)3·6H2O, Sm(NO3)3·6H2O, Eu(NO3)3·6H2O, Gd(NO3)3·6H2O, Tm(NO3)3·6H2O, Ce(NO3)3·6H2O and Yb(NO3)3·6H2O; the transition metal nitrate Me(NO3)2 is any one of Mg(NO3)2, Fe(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zr(NO3)2 and Zn(NO3)2.
[0015] Preferably, in step S2, the molar amount of citric acid monohydrate is 1 to 10 times the total molar amount of metal ions in the mixed nitrate solution;
[0016] Heat and stir at 65-100°C and evaporate to obtain a transparent gel.
[0017] Preferably, in step S3, the drying condition is: placing the gel in an oven at 50-200° C. for 5-12 hours.
[0018] Preferably, in step S4, the first high temperature treatment lasts for 1 to 5 hours.
[0019] Preferably, in step S5, the second high temperature treatment is performed for 1 to 10 hours.
[0020] Preferably, in step S5, the molten salt is a mixture of NaCl and KCl, and the total mass of the molten salt is 2 to 20 times the mass of the precursor.
[0021] The present invention also provides a magnetoplumbite-type oxide, which is prepared by the above-mentioned preparation method. The oxide has a magnetoplumbite structure, and the chemical formula of the magnetoplumbite-type oxide is LnMeAl 11 O 19 , wherein Ln is any one of the rare earth elements Y, La, Pr, Nd, Sm, Eu, Gd, Tm, Ce and Yb, and Me is any one of the transition metal elements Mg, Fe, Co, Ni, Cu, Zr and Zn.
[0022] The present invention also provides the use of the above-mentioned magnetoplumbite-type oxide as a catalyst material in sulfur reduction electrocatalysis. Further preferably, the above-mentioned magnetoplumbite-type oxide can be used to prepare lithium-sulfur batteries, and the above-mentioned magnetoplumbite-type oxide can be used as a catalyst material for lithium-sulfur batteries.
[0023] The beneficial effects of the present invention are:
[0024] The present invention combines the sol-gel method and the molten salt method to prepare the magnetoplumbite-type oxide LnMeAl 11 O 19 Compared with oxides prepared by other single methods (such as solid phase method, sol-gel method and molten salt method), the LnMeAl prepared by the present invention has a 11 O 19 It has stronger catalytic activity, can significantly improve the reaction kinetics of sulfur-based batteries, and is expected to give full play to the stable cycle performance of batteries at high rates. In addition, the preparation method of the present invention has the advantages of low cost, simplicity and wide application range. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0026] Figure 1 The XRD pattern of the magnetoplumbite oxide material prepared in Example 1;
[0027] Figure 2 The SEM morphology of the magnetoplumbite oxide material prepared in Example 2;
[0028] Figure 3 The electrocatalytic performance of the magnetoplumbite-type oxide material prepared in Example 3;
[0029] Figure 4 The electrocatalytic performance of the magnetoplumbite-type oxide material prepared in Example 4;
[0030] Figure 5 The electrocatalytic performance of the magnetoplumbite-type oxide material prepared in Example 5;
[0031] Figure 6 The electrocatalytic performance of the magnetoplumbite-type oxide material prepared in Example 6;
[0032] Figure 7 The battery cycle performance of the magnetoplumbite-type oxide material prepared in Example 7;
[0033] Figure 8 The SEM morphology of the product prepared in Comparative Example 1;
[0034] Fig. 9 XRD pattern of the product prepared in Comparative Example 2;
[0035] Fig.10 This is the electrocatalytic performance of the product prepared in Comparative Example 2. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0037] Example 1
[0038] This embodiment provides a method for preparing a magnetoplumbite-type oxide based on a sol-gel precursor method:
[0039] Sm(NO3)3·6H2O, Mg(NO3)2 and Al(NO3)3 were weighed and dissolved in deionized water in a molar ratio of 1:1:11, and the total concentration of the obtained mixed nitrate solution was 0.1 g / L. After stirring for 10 minutes, citric acid monohydrate with a molar number of 5 times the total number of metal ions was added to the nitrate solution obtained above, heated and stirred at 80°C, and rotary evaporated to obtain a transparent gel.
[0040] The above gel was placed in an oven at 155°C and kept warm for 7 hours until a loose and porous dry gel was observed.
[0041] The dry gel was then loaded into an alumina crucible and placed in a muffle furnace, and heated at 850° C. in an air atmosphere for 2 h to obtain a precursor.
[0042] The precursor was ground and crushed, and then mixed with molten salt (molar ratio NaCl: KCl = 1:1) with a weight ratio of 10 times, and then put into an alumina crucible, and placed in a muffle furnace, and heated at 1550 ° C in an air atmosphere for 1 h to obtain SmMgAl 11 O 19 Powder.
[0043] After analysis: the XRD spectrum of the prepared magnetoplumbite oxide is as follows Figure 1 As shown. It can be seen that the prepared powder is SmMgAl 11 O 19 , there is no other metal compound impurity phase on the matrix.
[0044] Example 2
[0045] This embodiment provides a method for preparing a magnetoplumbite-type oxide based on a sol-gel precursor method:
[0046] Eu(NO3)3·6H2O, Co(NO3)2 and Al(NO3)3 were weighed and dissolved in deionized water in a molar ratio of 1:1:11, and the total concentration of the obtained mixed nitrate solution was 0.3 g / L. After stirring for 10 minutes, citric acid monohydrate with a molar number of 6 times the total number of metal ions was added to the nitrate solution obtained above, heated and stirred at 75°C, and rotary evaporated to obtain a transparent gel.
[0047] The above gel was placed in an oven at 135°C and kept warm for 9 hours until a loose and porous dry gel was observed.
[0048] The dry gel was then loaded into an alumina crucible and placed in a muffle furnace. The crucible was heated at 875° C. in an air atmosphere for 2.5 h to obtain a precursor.
[0049] The above precursor was ground and crushed, and then ground and mixed evenly with molten salt (molar ratio NaCl: KCl = 1:1) with a weight ratio of 12 times, and then loaded into an alumina crucible and placed in a muffle furnace. Under the heating condition of 1575 ° C, in an air atmosphere, it was heated for 6 hours to obtain EuCoAl 11 O 19 Powder.
[0050] After analysis: the scanning electron microscope spectrum of the prepared magnetoplumbite oxide is as follows Figure 2 As shown, the prepared powder particles are observed to be small and uniform particles under SEM, and the size of a single particle is 600-800nm.
[0051] Example 3
[0052] This embodiment provides a method for preparing a magnetoplumbite-type oxide based on a sol-gel precursor method:
[0053] Sm(NO3)3·6H2O, Mg(NO3)2 and Al(NO3)3 were weighed and dissolved in deionized water in a molar ratio of 1:1:11, and the total concentration of the obtained mixed nitrate solution was 0.25 g / L. After stirring for 10 minutes, 6.6 times the total molar number of metal ions of monohydrated citric acid were added to the nitrate solution obtained above, heated and stirred at 90°C, and rotary evaporated to obtain a transparent gel.
[0054] The above gel was placed in an oven at 100°C for 7.5 hours until a loose and porous dry gel was obtained.
[0055] The dry gel was then loaded into an alumina crucible and placed in a muffle furnace. The crucible was heated at 820° C. in an air atmosphere for 3 h to obtain a precursor.
[0056] The precursor was ground and crushed, and then mixed with molten salt (molten salt ratio NaCl: KCl = 1:1) with a weight ratio of 11 times, and then put into an alumina crucible, and placed in a muffle furnace, and heated at 1610 ° C in an air atmosphere for 2 hours to obtain SmMgAl 11 O 19 Powder.
[0057] In order to test the electrocatalytic activity of sulfur-based batteries, 80 wt.% of sulfur-containing electrode materials (30% SmMgAl 11 O 19 Powder, 70% sulfur), 10wt.% Super P and 10wt.% polyvinylidene fluoride (PVDF) are fully mixed in a mortar, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) (Aldrich, 99% battery grade) solvent is dropped into it. After stirring for 8 hours, a uniform slurry is obtained. Then, the slurry is evenly applied to the positive electrode collector and placed in a vacuum oven at 60°C for about 10 hours. After it cools to room temperature, it is cut into standard round electrode sheets on a puncher, and the mass is weighed for use. The button CR2016 half-cell is in a glove box filled with inert gas Ar (H2O and O2, <10 -5 %), the separator of the battery is a polymer material polypropylene (PP) separator, model Celgard 2400. High-purity Li sheet is used as the negative electrode. The electrolyte contains 1M LiTFSI and 1wt.% LiNO3, and the solvent is a mixed solution of DOL and DME (volume ratio is 1:1). Cyclic voltammetry test (CV, voltage range: 1.7-2.8V) was carried out using CHI760E electrochemical workstation.
[0058] After analysis, the electrocatalytic performance of the prepared magnetoplumbite oxide is as follows: Figure 3Two obvious reduction peaks appear in the discharge platform of the reduction reaction, reaching the maximum value of the peak current at 2.289V and 1.981V, respectively, corresponding to the step-by-step lithiation reaction of the sulfur positive electrode, and the sulfur element is transformed into long-chain lithium polysulfide: S8→Li2S x (4≤x≤8) and long-chain lithium polysulfides are transformed into short-chain lithium polysulfides: Li2S x (4≤x≤8)→Li2S x (1≤x≤3). It can be seen that the prepared SmMgAl 11 O 19 As an electrocatalyst for sulfur-based batteries, it exhibits good performance.
[0059] Example 4
[0060] This embodiment provides a method for preparing a magnetoplumbite-type oxide based on a sol-gel precursor method:
[0061] Ce(NO3)3·6H2O, Ni(NO3)2 and Al(NO3)3 were weighed and dissolved in deionized water in a molar ratio of 1:1:11, and the total concentration of the obtained mixed nitrate solution was 0.45 g / L. After stirring for 10 minutes, 9 times the total molar number of metal ions of monohydrated citric acid were added to the nitrate solution obtained above, heated and stirred at 95°C, and rotary evaporated to obtain a transparent gel.
[0062] The above gel was placed in an oven at 175°C and kept warm for 8 hours until a loose and porous dry gel was observed.
[0063] The dry gel was then loaded into an alumina crucible and placed in a muffle furnace, and heated at 870° C. in an air atmosphere for 2 h to obtain a precursor.
[0064] The precursor was ground and crushed, and then mixed with molten salt (molar ratio NaCl: KCl = 1:1) with a weight ratio of 12 times, and then put into an alumina crucible, and placed in a muffle furnace, and heated at 1600 ° C in an air atmosphere for 2 hours to obtain CeNiAl 11 O 19 Powder.
[0065] A sulfur-based battery was prepared according to the method in Example 3, wherein the magnetoplumbite oxide was replaced by CeNiAl 11 O 19 Powder. Cyclic voltammetry (CV, voltage range: 1.7-2.8 V) was performed using a CHI760E electrochemical workstation.
[0066] After analysis, the electrocatalytic performance of the prepared magnetoplumbite oxide is as follows: Figure 4Two obvious reduction peaks appear in the discharge platform of the reduction reaction, reaching the maximum value of the peak current at 2.283V and 1.976V, respectively, corresponding to the step-by-step lithiation reaction of the sulfur positive electrode, and the sulfur element is transformed into long-chain lithium polysulfide: S8→Li2S x (4≤x≤8) and long-chain lithium polysulfides are transformed into short-chain lithium polysulfides: Li2S x (4≤x≤8)→Li2S x (1≤x≤3). It can be seen that the prepared CeNiAl 11 O 19 As an electrocatalyst for sulfur-based batteries, it exhibits good performance.
[0067] Example 5
[0068] This embodiment provides a method for preparing a magnetoplumbite-type oxide based on a sol-gel precursor method:
[0069] La(NO3)3·6H2O, Mg(NO3)2 and Al(NO3)3 were weighed and dissolved in deionized water in a molar ratio of 1:1:11, and the total concentration of the obtained mixed nitrate solution was 0.1 g / L. After stirring for 10 minutes, 3 times the total molar number of metal ions of monohydrated citric acid were added to the nitrate solution obtained above, heated and stirred at 70°C, and rotary evaporated to obtain a transparent gel.
[0070] The above gel was placed in an oven at 80°C and kept warm for 5 hours until a loose and porous dry gel was observed.
[0071] The dry gel was then loaded into an alumina crucible and placed in a muffle furnace. The crucible was heated at 750° C. in an air atmosphere for 2 h to obtain a precursor.
[0072] The precursor was ground and crushed, and then mixed with molten salt (NaCl: KCl = 1:1) with a weight ratio of 8 times, and then put into an alumina crucible, and placed in a muffle furnace, and heated at 1600 ° C in an air atmosphere for 3.5 hours to obtain LaMgAl 11 O 19 Powder.
[0073] A sulfur-based battery was prepared according to the method in Example 3, wherein the magnetoplumbite oxide was replaced by LaMgAl 11 O 19 Powder. Cyclic voltammetry (CV, voltage range: 1.7-2.8 V) was performed using a CHI760E electrochemical workstation.
[0074] After analysis, the electrocatalytic performance of the prepared magnetoplumbite oxide is as follows: Figure 5Two obvious reduction peaks appear in the discharge platform of the reduction reaction, reaching the maximum value of the peak current at 2.213V and 1.856V, respectively, corresponding to the step-by-step lithiation reaction of the sulfur positive electrode, and the sulfur element is transformed into long-chain lithium polysulfide: S8→Li2S x (4≤x≤8) and long-chain lithium polysulfides are transformed into short-chain lithium polysulfides: Li2S x (4≤x≤8)→Li2S x (1≤x≤3). It can be seen that the prepared LaMgAl 11 O 19 As an electrocatalyst for sulfur-based batteries, it exhibits good performance.
[0075] Example 6
[0076] This embodiment provides a method for preparing a magnetoplumbite-type oxide based on a sol-gel precursor method:
[0077] Gd(NO3)3·6H2O, Zn(NO3)2 and Al(NO3)3 were weighed and dissolved in deionized water in a molar ratio of 1:1:11, and the total concentration of the obtained mixed nitrate solution was 0.5 g / L. After stirring for 10 minutes, 5.5 times the total molar number of metal ions of monohydrated citric acid were added to the nitrate solution obtained above, heated and stirred at 80°C, and rotary evaporated to obtain a transparent gel.
[0078] The above gel was placed in an oven at 165°C and kept warm for 6 hours until a loose and porous dry gel was observed.
[0079] The dry gel was then loaded into an alumina crucible and placed in a muffle furnace. The crucible was heated at 900° C. in an air atmosphere for 2 h to obtain a precursor.
[0080] The precursor was ground and crushed, and then mixed with molten salt (molten salt ratio NaCl: KCl = 1:1) with a weight ratio of 10 times, and then put into an alumina crucible, and placed in a muffle furnace, and heated at 1500 ° C in an air atmosphere for 2.5 hours to obtain GdZnAl 11 O 19 Powder.
[0081] A sulfur-based battery was prepared according to the method in Example 3, wherein the magnetoplumbite oxide was replaced by the GdZnAl 11 O 19 Powder. Cyclic voltammetry (CV, voltage range: 1.7-2.8 V) was performed using a CHI760E electrochemical workstation.
[0082] After analysis, the electrocatalytic performance of the prepared magnetoplumbite oxide is as follows: Figure 6Two obvious reduction peaks appear in the discharge platform of the reduction reaction, reaching the maximum value of the peak current at 2.246V and 1.952V, respectively, corresponding to the step-by-step lithiation reaction of the sulfur positive electrode, and the sulfur element is transformed into long-chain lithium polysulfide: S8→Li2S x (4≤x≤8) and long-chain lithium polysulfides are transformed into short-chain lithium polysulfides: Li2S x (4≤x≤8)→Li2S x (1≤x≤3). It can be seen that the prepared GdZnAl 11 O 19 As an electrocatalyst for sulfur-based batteries, it exhibits good performance.
[0083] Example 7
[0084] This embodiment provides a method for preparing a magnetoplumbite-type oxide based on a sol-gel precursor method:
[0085] Eu(NO3)3·6H2O, Mg(NO3)2 and Al(NO3)3 were weighed and dissolved in deionized water in a molar ratio of 1:1:11, and the total concentration of the obtained mixed nitrate solution was 0.6 g / L. After stirring for 10 minutes, 7 times the total molar number of metal ions of monohydrated citric acid were added to the nitrate solution obtained above, heated and stirred at 90°C, and rotary evaporated to obtain a transparent gel.
[0086] The above gel was placed in an oven at 160°C and kept warm for 7 hours until a loose and porous dry gel was obtained.
[0087] The dry gel was then loaded into an alumina crucible and placed in a muffle furnace, and heated at 850° C. in an air atmosphere for 2 h to obtain a precursor.
[0088] The above precursor was ground and crushed, and then ground and mixed evenly with molten salt (molar ratio NaCl: KCl = 1:1) with a weight ratio of 9 times, and then put into an alumina crucible, and placed in a muffle furnace, and heated at 1550 ° C in an air atmosphere for 3.5 hours to obtain EuMgAl 11 O 19 Powder.
[0089] After analysis, the prepared magnetoplumbite oxide was subjected to melt sulfurization at 155°C to obtain the sulfur storage cathode material EuMgAl 11 O 19 / S, the long cycle performance of the assembled button cell is as follows Figure 7 As shown. When the current is increased and the cycle period is extended, EuMgAl 11 O 19 The / S composite electrodes showed more stable high-rate performance, 3.7 mg / cm 2The charge and discharge at a current density of 2C can be stably cycled for at least 560 cycles under high area loading.
[0090] Comparative Example 1
[0091] Eu(NO3)3·6H2O, Co(NO3)2 and Al(NO3)3 were weighed and dissolved in deionized water in a molar ratio of 1:1:11, and the total concentration of the obtained mixed nitrate solution was 0.3 g / L. After stirring for 10 minutes, citric acid monohydrate with a molar number of 6 times the total number of metal ions was added to the nitrate solution obtained above, heated and stirred at 75°C, and rotary evaporated to obtain a transparent gel;
[0092] The above gel was placed in an oven at 135°C and kept warm for 9 hours until a loose and porous dry gel was observed.
[0093] The dry gel was then loaded into an alumina crucible and placed in a muffle furnace. The crucible was heated at 875° C. in an air atmosphere for 2.5 h to obtain a precursor.
[0094] The above precursor was ground and placed in a muffle furnace, heated at 1575°C in an air atmosphere for 6 h to obtain EuCoAl 11 O 19 Powder.
[0095] After analysis: the SEM spectrum of the prepared product is as follows Figure 8 As shown. The magnetoplumbite oxide sintered by a single solid phase method has a large number of agglomerates, not fine, uniform nano-scale particles. Compared with Example 2, when the synthesis conditions do not include the relevant treatment operation of molten salt grinding and mixing, the prepared powder morphology is not fine, uniform particles.
[0096] Comparative Example 2
[0097] Metal oxide Sm2O3, FeO and Al2O3 powders were weighed respectively in a molar ratio of 1:2:22, and the powders were mixed in a planetary ball mill. The obtained mixed powders were loaded into an alumina crucible and placed in a muffle furnace. The mixture was heated at 1600°C in an air atmosphere for 4 hours to obtain a powder.
[0098] After analysis: the XRD pattern of the prepared product is as follows Fig. 9 As shown. It can be seen that the prepared powder cannot obtain pure phase SmFeAl 11 O 19 , and also contains other metal compound impurities Al2O3 and FeAl2O4.
[0099] A sulfur-based battery was prepared according to the method in Example 3, and the magnetoplumbite oxide was replaced with the powder prepared in this comparative example. Cyclic voltammetry (CV, voltage range: 1.7-2.8 V) was conducted using a CHI760E electrochemical workstation.
[0100] The electrocatalytic performance of the prepared products is shown in Fig.10 In the discharge platform of the reduction reaction, only one reduction peak appears, reaching the maximum value of the peak current at 2.165V, which corresponds to the lithiation reaction of the sulfur positive electrode, and the sulfur element is converted into lithium polysulfide: S8→Li2S x (1≤x≤8). It can be seen that when the synthesis conditions are not strictly in accordance with the claims (sol-gel method + molten salt), the prepared powder morphology is not fine and uniform particles, SmFeAl 11 O 19 It did not show good electrocatalytic performance.
[0101] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.
Claims
1. A method for preparing a magnetoplumbite-type oxide, characterized in that: The following steps are involved: S1, dissolving rare earth nitrate Ln(NO3)3·6H2O, transition metal nitrates Me(NO3)2 and Al(NO3)3 in deionized water to obtain a mixed nitrate solution; S2, adding citric acid monohydrate to the mixed nitrate solution obtained in step S1, heating and stirring, and evaporating to obtain a transparent gel; S3, drying the gel obtained in step S2 to obtain a loose and porous dry gel; The dry gel obtained in steps S4 and S3 is subjected to a first high temperature treatment at 650 to 950° C. in an air atmosphere to obtain a precursor; S5. Grind and crush the precursor obtained in step S4, grind and mix it evenly with molten salt, and then perform a second high-temperature treatment at 1500-2000° C. in an air atmosphere to obtain a magnetoplumbite-type oxide.
2. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of rare earth nitrate Ln(NO3)3·6H2O, transition metal nitrate Me(NO3)2 and Al(NO3)3 is 1:1:11; the total concentration of the prepared mixed nitrate solution is 0.01-1 g / L.
3. The preparation method according to claim 1, characterized in that: In step S1, the rare earth nitrate Ln(NO3)3·6H2O is any one of Y(NO3)3·6H2O, La(NO3)3·6H2O, Pr(NO3)3·6H2O, Nd(NO3)3·6H2O, Sm(NO3)3·6H2O, Eu(NO3)3·6H2O, Gd(NO3)3·6H2O, Tm(NO3)3·6H2O, Ce(NO3)3·6H2O and Yb(NO3)3·6H2O; the transition metal nitrate Me(NO3)2 is any one of Mg(NO3)2, Fe(NO3)2, Co(NO3)2, Ni(NO3)2, Cu(NO3)2, Zr(NO3)2 and Zn(NO3)2.
4. The preparation method according to claim 1, characterized in that: In step S2, the molar amount of citric acid monohydrate is 1 to 10 times the total molar amount of metal ions in the mixed nitrate solution; Heat and stir at 65-100°C and evaporate to obtain a transparent gel.
5. The preparation method according to claim 1, characterized in that: In step S3, the drying condition is: placing the gel in an oven at 50-200° C. for 5-12 hours.
6. The preparation method according to claim 1, characterized in that: In step S4, the first high temperature treatment lasts for 1 to 5 hours.
7. The preparation method according to claim 1, characterized in that: In step S5, the second high temperature treatment is performed for 1 to 10 hours.
8. The preparation method according to claim 1, characterized in that: In step S5, the dissolved salt is a mixture of NaCl and KCl, and the total mass of the dissolved salt is 2 to 20 times the mass of the precursor.
9. A magnetoplumbite-type oxide, characterized in that: The preparation method according to any one of claims 1 to 8 is used to prepare the magnetoplumbite-type oxide, the chemical formula of which is LnMeAl 11 O 19 , wherein Ln is any one of the rare earth elements Y, La, Pr, Nd, Sm, Eu, Gd, Tm, Ce and Yb, and Me is any one of the transition metal elements Mg, Fe, Co, Ni, Cu, Zr and Zn.
10. Use of the magnetoplumbite-type oxide according to claim 9 as a catalyst material in a sulfur reduction reaction.
Citation Information
Patent Citations
High induction grain-oriented la-doped strontium ferrite and preparation method thereof
CN105600827A
Potassium-doping lanthanum manganite / graphene composite wave-absorbing material and manufacture method thereof
CN106554753A
Preparation method of hexaaluminate catalysts with high specific surface areas
CN108097242A
Highly active catalyst for electro-catalytic reaction and preparation method thereof
CN110635143A
Rare earth element doped Z-type ferrite material and preparation method thereof
CN115925407A
Cited By
Preparation method and application of yttrium zirconate-based thermal insulation coating powder with high near-infrared reflectivity and high entropy
CN119929873A
